The effects of milk as a food matrix for polyphenols on the excretion profile of cocoa ( − )-epicatechin metabolites in healthy human subjects - Roura, Elena; Andrés-Lacueva, Cristina; Estruch, Ramon; Lourdes Mata Bilbao, M.; Izquierdo-Pulido, Maria; Lamuela-Raventós, Rosa M. (British journal of nutrition, 2008)
The effect of different food matrices on the metabolism and excretion of polyphenols is uncertain. The objective of the study was to evaluate the possible effect of milk on the excretion of ( − )-epicatechin metabolites from cocoa powder after its ingestion with and without milk. Twenty-one volunteers received the following three test meals each in a randomised cross–over design with a 1-week interval between meals: (1) 250 ml whole milk as a control; (2) 40 g cocoa powder dissolved in 250 ml whole milk (CC–M); (3) 40 g cocoa powder dissolved in 250 ml water (CC–W). Urine was collected before consumption and during the 0–6, 6–12 and 12–24 h periods after consumption. ( − )-Epicatechin metabolite excretion was measured using liquid chromatography–MS. One ( − )-epicatechin glucuronide and three ( − )-epicatechin sulfates were detected in urine excreted after the intake of the two cocoa beverages (CC–M and CC–W). The results show that milk does not significantly affect the total amount of metabolites excreted in urine. However, differences in metabolite excretion profiles were observed; there were changes in the glucuronide and sulfate excretion rates, and the sulfation position between the period of excretion and the matrix. The matrix in which polyphenols are consumed can affect their metabolism and excretion, and this may affect their biological activity. Thus, more studies are needed to evaluate the effect of these different metabolite profiles on the body.